CD44-targeted virus-mimicking nanomedicine eliminates cancer stem cells and mitigates chemoresistance in head and neck squamous cell carcinoma - Yiwen Chen; Zhen Qin; Yujia Wang; Baoxin Gu; Jing Wang; Yunfei Zheng; Yuting Niu; Lingfei Jia (Materials Today Bio)
Cancer stem cells (CSCs) play critical roles in tumor growth, metastasis, and chemoresistance. Although several small-molecule inhibitors designed to inhibit CSCs have been investigated in clinical trials, their inadequate tumor targeting and potential off-target side effects have led to poor outcomes. A CD44-targeted virus-mimicking nanomedicine encapsulating the BMI1 inhibitor PTC209 (PTC209@VNP-HA) was designed to treat head and neck squamous cell carcinoma (HNSCC). We used a dendritic mesoporous silica nanoparticle (MSN) as the core for virus-mimicking nanoparticle (VNP) formation after adding shell particles to the MSN surface. The VNP surface was then modified with hyaluronic acid (HA), and PTC209 was adsorbed by mesopores to form PTC209@VNP-HA. In this system, HA is used to target CD44+ CSCs. The rough surface of VNP-HA provided better drug delivery efficiency than smooth nanoparticles modified with HA. VNP-HA enhanced the cancer inhibitory effect of PTC209 12-fold compared to the administration of free PTC209, leading to significantly higher bioavailability of PTC209. Both in vitro and in vivo assays showed that PTC209@VNP-HA inhibited cancer stemness, proliferation, and metastasis in HNSCC. Mechanistically, this inhibitory effect is closely associated with DNA damage/apoptosis signaling. Using a series of preclinical models in murine systems, we confirmed that PTC209@VNP-HA eliminated BMI1+ CSCs, and greatly inhibited the proliferation and metastasis of HNSCC when combined with cisplatin. This study investigated PTC209@VNP-HA as a novel and potentially transformative HNSCC treatment option that eliminates CSCs, prevents metastasis, and overcomes cisplatin resistance.